Application of Spiral Antennas for Perspective Vehicle-Board Systems and Complexes - Gadzhiev, Elchin; Skripachev, Vladimir; Generalov, Alexander; Polushkovskiy, Yuri; Tumanov, Mikhail; Zhukov, Alexander (2018 Engineering and Telecommunication (EnT-MIPT), 2018)
At present, there is a need for vehicle-board antenna system of COSPAS-SARSAT. The antenna system consists of a transmitting antenna and a receiving antenna. In this paper the antenna system of COSPAR-SARSAT for space vehicles of series "Meteor-M" is designed and presented. In addition to receiving and transmitting antennas, testing complex for full-scale test has been developed. In this paper the results of measurement of voltage standing-wave ratio, radiation pattern, gain of vehicle-board antennas are presented. The obtained results satisfy the technical task for the antenna system for vehicle-board equipment COSPAS-SARSAT.